The ‘right to the city’ and its recognition in the Peruvian legal system - Rioja García, Luis Fernando (2021)
The following article evidences the importance of considering the concept and the components of the right to the city in the Peruvian legislation. For that purpose, it considers the growing recognition of the importance of cities under the ‘New Urban Agenda’ and the search for assurance of decent life quality for the inhabitants of a city. Moreover, the authors propose to overcome the conception of the city as a physical space where its sole purpose is to produce individual wealth and benefits, for its recognition as a space of interaction and citizen development as a collectivity. Based on this definition, the right to the city implies a guiding principle that seeks to generate spaces for community participation, a fair distribution of urban charges and benefits, and the promotion of active citizenship.